Macro disagreement and the cross-section of stock returns - LI, Frank Weikai (Institutional Knowledge at Singapore Management University, 2016)
This paper examines the effects of macro-level disagreement on the cross-section of stock returns. Using forecast dispersion measure from Survey of Professional Forecasters database, I find that when forecast dispersion on macroeconomic factor is high, stocks that have high loadings on that factor earn lower future returns relative to stocks with low loadings and vice versa. This negative relationship between risk premium of macro-factors and macro-level disagreement is robust and exists for a large set of macroeconomic risk factors. These findings are consistent with the model of Hong and Sraer (2015), where high beta stocks are more prone to speculative mispricing than low beta stocks due to their greater sensitivity to aggregate disagreement, resulting in lower subsequent returns for high beta stocks during high aggregate disagreement states.